Credit of ecclesiastical origin in the city of Cordoba, 1800 - 1830 - Tedesco, Elida (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2001)
We propose to carry out a study of the credit granted by the Church of the city of Cordoba between 1800 and 1830, basing our research on the ecclesiastical credit contracts registered before the notary. The objective is to analyze the fluctuations of ecclesiastical credit in relation to the transformations suffered by the regional economic situation, but also considering the relationship with the political changes of the period affecting the Church. In addition, we will study the credit mechanisms used and the main lenders. We intend to specify the effects on the development of credit of ecclesiastical origin of a first economic period (1800-1810) of relative prosperity of the export sector and stable trade balance and of a second moment (1811-1830) of crisis of the export sector and monetary shortage. At the same time, we will contemplate in our analysis the institutional and economic instability that affected the Church of Cordoba during these three decades, in the first one as a result of the colonial royalist policy and, in the following two, as a consequence of the economic demands and the interventions in ecclesiastical affairs by the national and provincial governments.